The Effectiveness of Sign Language in Media Accessibility: Bridging the Communication Gap for the Hearing Impaired - Taeza, Jordan R. (Journal of Cultural Analysis and Social Change, 2025)
This paper explores how sign language interpretation can be beneficial in improving access to the media by the deaf and hard-of-hearing (DHH) communities. In spite of the technological progress and increased awareness of the rights to accessibility, media spaces still pose a problem to people who use visual means of communication. A quantitative, descriptive, cross-sectional survey, a type of study, was used to collect data in 300 participants with a different level of hearing impairment. The structured questionnaire included demographic factors, the pattern of media usage, perception of interpreter visibility, clarity, synchronization, and preference of different modalities of accessibility. The descriptive statistics showed that the mean scores were high in all the variables of accessibility implying that sign language interpretation is greatly acceptable to the users. The reliability analysis yielded a Cronbach alpha of 0.91 and it depicts high internal consistency in the effectiveness scale. Correlation analysis also revealed that there were positive association between the visibility, clarity, synchronization, understanding, and inclusion, which indicated that various dimensions of sign language accessibility interact harmoniously to enable the user involvement. These findings were supported by open-ended responses, where the most frequent problems were the small size of interpreter windows and lack of uniform synchronization. Participants indicated that they highly preferred multimodal accessibility formats which have a combination of sign language and subtitles. This paper finds that sign language is an essential part of inclusive media design and should use standardized practices, enhance technical execution and extend its integration to television and digital platforms in order to support DHH audiences more effectively.